Penerapan Manajemen Strategi Meggunkan Metode SWOT dan QSPM pada Industri Kendang Jimbe UD. Karya Mandiri - Abdillah, Moch. Rizki; Mahariani, Yeni Roha (Jurnal Studi Multidisiplin Qomaruna, 2025)
In facing increasingly tight industrial competition, MSMEs are required to implement the right business strategy to maintain their existence and increase their competitiveness. This study aims to apply strategic management to MSMEs of Kendang Jimbe craftsmen UD. Karya Mandiri in Blitar City using the SWOT method and Quantitative Strategic Planning Matrix (QSPM). SWOT analysis is used to identify internal factors in the form of strengths and weaknesses, as well as external factors in the form of opportunities and threats that affect business performance, while QSPM is used to determine priority strategies based on their level of attractiveness. This study uses a quantitative descriptive approach with data collection techniques through observation, interviews, and questionnaires to owners, employees, and consumers of UD. Karya Mandiri. The results of the analysis show that the main strength of this MSME lies in high product quality and good reputation, while its main weakness is the limited digital promotion. Opportunities that can be utilized are the increasing interest of the international market in traditional musical instruments, while threats include fluctuations in raw material prices and competition from similar products. Based on the IFE and EFE matrix analysis, UD. Karya Mandiri's position is in quadrant I in the SWOT diagram, which shows the potential to implement an aggressive strategy through expansion. The priority strategy resulting from the QSPM is export optimization by utilizing product quality, which obtained a Total Attractiveness Score (TAS) of 3.42. This strategy is expected to expand market share while strengthening the Kendang Jimbe brand image in the global market. Academically, this study contributes to the application of strategic management in culture-based MSMEs, as well as offering practical recommendations that can be used as a reference for similar MSMEs in responding to modern market challenges sustainably.